The Ancient Tantric in Balinese Contemporary Art - I Wayan Karja; Roni Feldman (Universitas Udayana, 2024)
In recent years, artists from various cultures have increasingly drawn on the spiritual and philosophical principles of ancient tantra. This article explores the influence of ancient tantric traditions on contemporary Balinese arts. It employed an innovative art-based research methodology utilizing qualitative, interpretive, and practice-based research methods. These included observation, interviews, and document analysis while integrating theoretical frameworks, symbolic perspectives, and theo-aesthetic considerations. The research reveals how artists transform and reinterpret tantric themes in their work, highlighting the complex relationship between modern expressions and ancient inspirations. Balinese art, as the study shows, achieves beauty by blending opposites, such as masculine and feminine qualities, through the concept of lanang-wadon. By examining this topic, the research provides valuable insights into the evolving relationship between spirituality, creativity, and cultural exchange in Bali and the interconnected world. This study underscores the dynamic interplay between ancient traditions and contemporary artistic practices, showcasing a unique fusion that enriches both the art and its cultural context.